2023
DOI: 10.1002/ps.7393
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some agricultural treatments on the Egyptian alfalfa weevil, Hypera brunneipennis and their economic evaluation on yield and yield components in Egypt

Abstract: BACKGROUND: The Egyptian alfalfa weevil, Hypera brunneipennis causes damage on different parts of alfalfa plants. Therefore, four agricultural treatments are carried out included calcium super phosphate addition (15.5% P 2 O 5 ), potassium sulphate addition (50% K 2 O), microelements spraying and hand removing of weeds to reduce the population of the Egyptian alfalfa weevil and increase both the final yield and obtain a healthy plant. RESULTS:The treatment of calcium super phosphate (15.5% P 2 O 5 ), potassium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…Several authors recorded the insect pests in their samples from clover fields in Egypt. Among them are Rakha( 2008) at KAfr El-sheikh, Awadalla et al (2014) at Dakahlia Governorate and Kandil et al, (2023) at Nubaria, Beheira Governorate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors recorded the insect pests in their samples from clover fields in Egypt. Among them are Rakha( 2008) at KAfr El-sheikh, Awadalla et al (2014) at Dakahlia Governorate and Kandil et al, (2023) at Nubaria, Beheira Governorate.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the several problems of insecticide applications against insect pests, in general, and against clover insects in particular, it has become necessary to minimize such applications, and apply safe alternative methods. Kandil et al, (2023) in the clover fields recommended optimum fertilizer treatments in clover fields to encourage clover plants to withstand the damage of H. brunnipennis and they concluded that balanced application of calcium superphosphate, potassium sulphate, micronutrients, as well as weed control has improved clover growth and reduced the activity of the weevil. However, biological control agents proved to have relative efficiencies against larvae and adults of the weevil (Alizadeh 2017).…”
Section: Introductionmentioning
confidence: 99%